2022
DOI: 10.1186/s12885-022-09666-2
|View full text |Cite
|
Sign up to set email alerts
|

Mir-675-5p supports hypoxia-induced drug resistance in colorectal cancer cells

Abstract: Background The uncontrolled proliferation of cancer cells determines hypoxic conditions within the neoplastic mass with consequent activation of specific molecular pathways that allow cells to survive despite oxygen deprivation. The same molecular pathways are often the cause of chemoresistance. This study aims to investigate the role of the hypoxia-induced miR-675-5p in 5-Fluorouracil (5-FU) resistance on colorectal cancer (CRC) cells. Methods CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…A prevalent example is miR-675-5p, an miRNA with an established oncogenic role in CRC [ 56 ]. In particular, several studies have investigated the functional role of miR-675-5p in CRC, which is suggested to support hypoxia-induced EMT in colon cancer cells and promote CRC cell growth and drug resistance [ 24 , 26 , 27 ]. However, the clinical significance of miR-675-5p as a molecular marker has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A prevalent example is miR-675-5p, an miRNA with an established oncogenic role in CRC [ 56 ]. In particular, several studies have investigated the functional role of miR-675-5p in CRC, which is suggested to support hypoxia-induced EMT in colon cancer cells and promote CRC cell growth and drug resistance [ 24 , 26 , 27 ]. However, the clinical significance of miR-675-5p as a molecular marker has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Costa et al demonstrated that miR-675-5p is overexpressed in metastatic colon cancer cells, promoting EMT by controlling hypoxia-inducible factor 1 subunit alpha (HIF1a) [ 26 ]. In addition, the hypoxic tumor microenvironment in CRC induces the expression levels of miR-675-5p, thereby enhancing drug resistance [ 27 ]. It may seem counter-intuitive that miR-675-5p levels are downregulated in the majority of colorectal adenocarcinoma tissues compared to those in adjacent normal colorectal tissues, whereas miR-675-5p overexpression is being suggested as a predictor of adverse prognosis in this malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HIF has been reported to promote docetaxel resistance in triple-negative breast cancer cells by suppressing miR-494 expression to enhance Survivin expression [47]. Furthermore, HIF is known to cause oxaliplatin resistance in colorectal cancer by inducing miR-338-5p expression under hypoxia to promote IL-6 signaling, which, in turn, suppresses apoptosis via the STAT3/BCL2 pathway [48][49][50].…”
Section: Hif-mediated Mechanisms Behind Chemotherapy Resistancementioning
confidence: 99%
“…We have recently demonstrated that lncH19-derived miR-675-5p enforces hypoxia-induced chemoresistance to 5-FU by targeting pro-caspase-3 and inhibiting the pro-apoptotic effects of 5-FU (Zichittella et al, 2022).…”
Section: Introductionmentioning
confidence: 99%